Palladium catalyzed asymmetric reactions assisted by P*, P*-bidentate bisdiamidophosphites based on 1, 4-diols. Issue 5 (2nd February 2017) - Gavrilov, Konstantin N.; Zheglov, Sergey V.; Gavrilov, Vladislav K.; Maksimova, Marina G.; Tafeenko, Viktor A.; Chernyshev, Vladimir V.; Birin, Kirill P.; Mikhel, Igor S.
Abstract: A small series of P*, P* -bidentate bisdiamidophosphite ligands containing 1, 3, 2-diazaphospholidine rings have been prepared. The cationic [Pd(allyl)(P*, P*)]BF4 and neutral [Pd(P*, P*)Cl2 ] palladium(II) complexes were synthesized with one of the new ligands. The use of these ligands provides up to 98% ee in Pd-catalyzed asymmetric allylations of ( E )-1, 3-diphenylallyl acetate, up to 72% ee in Pd-catalyzed asymmetric alkylation of cinnamyl acetate with ethyl 2-oxocyclohexane-1-carboxylate and up to 94% ee in Pd-catalyzed desymmetrization of N, N' -ditosyl- meso -cyclopent-4-ene-1, 3-diol biscarbamate. The influence of the nature of the bridging ligand fragments of the bisdiamidophosphites on asymmetric induction is discussed. Graphical abstract: